Marketing Strategic: A Case Study On Cyberia Project - Chang, Tan Wang (2002)
Cyberia Project, a housing development project by a Paramoden Sdn Bhd, a subsidiary of the MK Land Group is a good point to study on it. Selling property in a new city, the hub of Multimedia Super Corridor-Cyberjaya is a tough job. The development of MSC, especially Cyberjaya is still under process. Its achivement is still an question mark to anyone who concern about it. But, indeed, Cyberia Project managed to achieved more than RM100 millions sales for year 2001. This paper study will focus on the marketing strategic implemented by Cyberia Management to achieved their goal.